Longevity, aging, and caloric restriction : Clive Maine McCay and the construction of a multidisciplinary research program - Park, Hyung Wook (2013)
Since the 1930s scientists from fields such as biochemistry, pathology, immunology, genetics, neuroscience, and nutrition have studied the relation of dietary caloric intake to longevity and aging. This paper discusses how Clive Maine McCay, a professor of animal husbandry at Cornell University, began his investigation of the topic and promoted it as a productive research program in the multidisciplinary science of gerontology. Initially, McCay observed the effect of reduced-calorie diets on life span and senescence while pursuing his nutrition research in the context of animal husbandry and agriculture. But when he received funding from the Rockefeller Foundation and started to participate in the establishment of gerontology during the 1930s, the scope of his research was considerably expanded beyond his original disciplinary domain. It became a multidisciplinary research program that attracted scholars from a variety of scientific and medical disciplines. This paper argues that through this expansion McCay's research created a means of maintaining cooperation among the diverse and heterogeneous academic fields constituting gerontology.